Vloga hidroksisteroid-dehidrogenaz pri uravnavanju aktivnosti estrogenov in progestagenov - Lanišnik-Rižner, Tea (Medicinski razgledi, 2004)
Endometrial cancer and endometriosis are very common estrogen-dependent diseases. Endometrial cancer is the third most common cancer in women, while endometriosis affects around 15-20% of women of reproductive age and leads to infertility in 30-50% of patients. The current hypothesis postulates that exposure to estrogens unopposed by progestagens increases the mitotic activityof endometrial cells and the number of errors during DNA replication that can lead to hyperplasia or a malignant phenotype. The activity of estrogens and progestagens is regulated at the receptor and pre-receptor levels, by interconversions between the active forms (estradiol, progesterone)and inactive forrns (estrone, 20alpha-hydroxyprogesterone). The enzymes which are responsible for these interconversions are 17 beta-hydroxysteroid dehydrogenase and 20alpha-hydroxysteroid dehydrogenase. The difference in the expression of these enzymes in endometrial cancer and endometriosis may lead to high estrogen concentrations and low progestagen concentrations, which could result in the development of endometrial cancer orendometriosis.
Keywords: ginekologija; endometrij; endometrioza; rak (medicina); hormoni; biokemija